2017
DOI: 10.1007/s12026-017-8953-8
|View full text |Cite
|
Sign up to set email alerts
|

Th2-biased immune response and agglutinating antibodies generation by a chimeric protein comprising OmpC epitope (323–336) of Aeromonas hydrophila and LTB

Abstract: Aeromonas hydrophila is responsible for causing fatal infections in freshwater fishes. Besides chemical/antibiotic treatment and whole-cell vaccine, no subunit vaccine is currently available for A. hydrophila. Outer membrane proteins of gram-negative bacteria have been reported as effective vaccine candidates. Peptide antigens elicit focused immune responses against immunodominant stretches of the antigen. We have attempted to characterize the immunogenicity of linear B-cell epitopes of outer membrane protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Western blotting was carried out as described earlier [ 31 ]. The cell lysates prepared from the uninduced and induced cultures or purified proteins were resolved by 12% SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blotting was carried out as described earlier [ 31 ]. The cell lysates prepared from the uninduced and induced cultures or purified proteins were resolved by 12% SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…For the isolation of splenocytes, immunized mice were sacrificed after 1 week of the second booster, i.e., on day 35 of primary immunization, and the spleen was surgically removed under aseptic conditions. The splenocytes were isolated as described earlier [ 31 ]. Splenocytes from the recombinant protein immunized mice and PBS-immunized mice (control) were seeded (1×10 6 cells/100 µl/well, in triplicates) in a 96-well culture plate and stimulated with respective protein (20 µg in 100 µl PBS).…”
Section: Methodsmentioning
confidence: 99%
“…83 against a broad spectrum of enteric bacteria. 75,85 Furthermore, the fusion of CTB with extracellular lectin from Aeromonas veronii elicited a more robust immune response in spotted sand bass (Paralabrax maculatofasciatus) after oral immunization than free antigen immobilized on latex microspheres. 86 Despite many promising indications, the positive effect of LTB and CTB on antigen uptake and subsequent activation of fish immunity is highly dependent on many factors, such as the nature of the host, pathogen, encapsulation method, and administration route.…”
Section: Bacterial Enterotoxins and Structural Proteinsmentioning
confidence: 99%
“…With this regard, Companjen et al 84 observed higher absorption of green fluorescent protein (GFP) fused with LTB by carp enterocytes complemented by retention of LTB‐GFP molecule by the macrophage‐like cells underlying the intestinal epithelium. Similarly, different epitopes of outer membrane protein C from Aeromonas hydrophila fused with LTB confers protection against a broad spectrum of enteric bacteria 75,85 . Furthermore, the fusion of CTB with extracellular lectin from Aeromonas veronii elicited a more robust immune response in spotted sand bass ( Paralabrax maculatofasciatus ) after oral immunization than free antigen immobilized on latex microspheres 86 .…”
Section: Strategies To Increase Oral Vaccines Efficiencymentioning
confidence: 99%
“…Generally, non-toxic HLTs (e.g., subunit-B and mutant forms of HLT) also act as immune adjuvants to activate DCs, B cells, and T cells, regulate epitope specificity, and improve the immune response (Batista et al, 2014; Rodrigues et al, 2011). The fusion of the HLT B subunit (HLTB) with the linear B cell epitope of the outer membrane protein (OmpC) of Aeromonas hydrophila can stimulate the production of neutralizing antibodies against this linear epitope and generate a Th2 type mixed auxiliary T cell immune response (Sharma et al, 2017). The two epitopes of the Zairian Ebola virus GP1 protein, which can be recognized by neutralizing antibodies, were coupled with HLTB protein to form recombinant antigen HLTB-EBOV expressed in plant tissues, and immunizing mice with the recombinant antigen presented by the plant induced a higher level of IgA and IgG responses (Rios-Huerta et al, 2017).…”
Section: Bacterial Toxin Proteinsmentioning
confidence: 99%